Creative and algorithmic reasoning – the role of strategy choices in practice and test - Bergqvist, Tomas; Norqvist, Mathias (NOMAD Nordic Studies in Mathematics Education, 2022)
This study is based on a framework of algorithmic and creative mathematical reasoning and focuses on students’ strategy choices in both practice and test. Previous research indicates that students that practice mathematics with tasks with given solution methods are outperformed in later test by students that have to construct solution methods during practice. Video recordings, students’ written solutions, and student interviews from ten university students provides data on strategy choices. The analysis was carried out to capture students’ strategy choices and reasons for these choices. The results showed that there was no real difference in how the students solved the tasks in the test. Regardless of practice condition, more or less the same solution strategies were used in the test situation.